Advances and challenges with data broadcasting in wireless mesh networks. - Chun Tung Chou (IEEE Communications magazine)
Wireless mesh networks have become a promising means to provide low-cost broadband access. Many WMN applications require broadcasting data (IPTV etc.) over the WMN. This article studies how efficient data broadcast, measured in terms of broadcast latency, can be realized by exploiting two features of WMNs: the use of multiple transmission rates at the link layer and the use of multiple radio interfaces on each node. We demonstrate that by exploiting these features, broadcast latency can be reduced severalfold compared to the current default practice in wireless LANs of using the lowest transmission rate for broadcast traffic. We also discuss two important insights we have gained from our investigation. First, we find that when multiple radio interfaces are used, a channel assignment algorithm designed for unicast traffic may often perform poorly for broadcast flows. Second, we find that the efficiency of a transmission rate for reducing broadcast latency can be reasonably predicted by the product of the transmission rate and its coverage area.